Assessment of Micro-Mechanical Variations in Experimental Arteriovenous Fistulae using Atomic Force Microscopy. Issue 3 (May 2016) - Laurito, Tyler; Sueiras, Vivian; Fernandez, Natasha; Escobar, Luis A.; Martinez, Laisel; Andreopoulos, Fotios; Salman, Loay H.; Vazquez-Padron, Roberto I.; Ziebarth, Noël M.
Purpose: This study presents a method to quantify micro-stiffness variations in experimental arteriovenous fistulae (AVF). Methods: AVF created by anastomosing the superficial epigastric vein to the femoral artery in Sprague-Dawley rats were allowed to remodel for 21 days before being harvested and preserved in culture medium. A custom atomic force microscope was used to measure microvascular stiffness (Young's modulus) in three areas of the AVF: the inflow artery, the juxta-anastomotic area, and the outflow vein. Morphometric measurements and collagen and elastin contents were also determined. Results: Atomic force microscopy indentation revealed an increased stiffness in the juxta-anastomotic area of the AVF compared to the outflow vein and inflow artery. The juxta-anastomotic area was also significantly stiffer than the contralateral vein. The lack of elasticity (higher Young's modulus) of the juxta-anastomotic region was associated with a thicker vascular wall that was rich in collagen but poor in elastin. Conclusions: This study demonstrates for the first time the feasibility of using atomic force microscopy to measure local stiffness variations in experimental AVF. This technique could be instrumental in advancing our understanding of how micro-spatial organization of the AVF wall determines the overall biomechanical performance of this type of vascular access.